AN ANALYSIS OF TIME ORIENTATION IN INFORMAL CONVERSATION OF TATEDE VILLEGES IN SUMBAWA REGENCY - Subaidah; Iwan Jazadi; Suparman (STKIP Paracendekia NW Sumbawa, 2023)
The purpose of the study was to analyzed and identify time orientation such as the past, present and future. The method was used in this research qualitative descriptive. This study focused on the used of time in everyday conversations. The object of this research is the community in Tatede village, Sumbawa Besar, West Nusa Tenggara. The researchers has took five conversations. Each conversation consists of 3-9 people. The techniques of data collection there are two ways of observation and interview. In this research, the researcher has found that the society of Tatede village was dominant used the past tenses . from the five conversations there were four different reasons. Such as the first and fifth conversations have the same reason the second, third and fourth have different reasons. The results of this study indicate that Tatede people have similarities with Asian countries such as China, Japan and Korea that is using the past tense in everyday conversation